Vom Verkünder des Gottesreiches zum Logos - und zurück?: Zur Rolle Jesu und des frühen Christentums im Gegendiskurs Abraham Geigers - Buchholz, René (Review of ecumenical studies, 2025)
Abraham Geiger's reclaiming of Jesus for Judaism is part of a counter-discourse and counter-history developed in the 19th century by representatives of the "Wissenschaft des Judentums" (Jewish Studies) theologians, and Jewish religious philosophers. This scholarly approach aimed to contribute to Jewish emancipation efforts, support the renewal of Judaism in the modern era, and, not least, refute the Christian claim of Judaism's inferiority. By claiming Jesus and his early followers, including Paul, for Judaism, Geiger not only highlights the gaps in contemporary Life-of-Jesus' research but also exposes the rupture between Jesus and his religious practice on the one hand and the religion that later invoked his name on the other. This finding has not been fully addressed by current dogmatic or Christological models.